2019
DOI: 10.1002/pchj.329
|View full text |Cite
|
Sign up to set email alerts
|

The linear and curvilinear relation between personality and subjective well‐being in visual artists: Perceived creation stress as a mediator

Abstract: The aims of this study were to investigate the associations among personality traits, perceived creation stress, and life satisfaction in visual artists, as well as examine the mediating role of perceived creation stress. We recruited 201 visual artists in Beijing's Songzhuang art colony to participate in this study and used the Mini International Personality Item Pool‐Five‐Factor Model measure, the Perceived Creation Stress Scale, and the Satisfaction with Life Scale. Extraversion and conscientiousness positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have shown that the relationships between artists’ personality traits and their happiness may differ from those of nonartists (Cameron et al, 2013; Cox et al, 2016; Croom, 2015). Specifically, a previous study on visual artists revealed curvilinear relationships between personality traits and life satisfaction (Chen et al, 2020). The results of this study provide more evidence supporting the hypothesis that the association between personality and subjective well-being goes beyond a simple linear relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the relationships between artists’ personality traits and their happiness may differ from those of nonartists (Cameron et al, 2013; Cox et al, 2016; Croom, 2015). Specifically, a previous study on visual artists revealed curvilinear relationships between personality traits and life satisfaction (Chen et al, 2020). The results of this study provide more evidence supporting the hypothesis that the association between personality and subjective well-being goes beyond a simple linear relationship.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, experienced artists perceive more information from paintings and show different eye scan paths than art novices (Koide et al, 2015) while greater expertise is related to greater perceived understanding of artworks (Mullennix & Robinet, 2018). Research examining the flourishing of artists has found that visual artists report experiencing symptoms of depression and high levels of stress (Daily et al, 2021) and that less desirable personality characteristics (e.g., neuroticism, low agreeableness) may be particularly important for visual artist flourishing (Chen et al, 2020). If we consider art expertise as multi-faceted (e.g., knowledge or training in art, interest in art; Specker et al, 2020), however, we may see differing relations with flourishing.…”
Section: Introductionmentioning
confidence: 99%